(untitled) (CIPEEX, 2022)
ANIMAL-ASSISTED THERAPY (AAT) IS AN UNCONVENTIONAL TYPE OF THERAPY THAT INCLUDES THE USE OF ANIMALS IN TREATMENT. NEVERTHELESS, IT IS A VALUABLE TECHNIQUE THAT HAS ITS IMPORTANCE SHOWN THROUGH THE TREATMENT OF A GREAT EXTENT OF PATHOLOGIES, AS SEEN IN CASES OF CHILDREN WITH MENTAL DISORDERS. AAT PROVIDES MEANS FOR A BETTER CARE AND UNDERSTANDING OF THE CHILD’S PATHOLOGY BECAUSE THROUGH AAT THE DOCTOR-PATIENT RELATIONSHIP GROWS STRONGER AND MORE SUSTAINABLE. THEREFORE, THIS LITERATURE REVIEW HAS SET AS ITS PREEMINENT AIM TO UNDERSTAND THE POSITIVE EFFECTS OF ANIMAL-ASSISTED THERAPY FOR NON-NEUROTYPICAL CHILDREN, BY MAKING A SHORT INTEGRATIVE REVIEW OF FIVE SELECTED ARTICLES. FURTHERMORE, IT IS MAJOR TO STATE THAT THE STUDY€™S PREMISE PERVADES THE PATIENT€™S SOCIAL DYNAMIC, IN PARTICULAR THE CHILDREN€™S INTERACTIONS IN REGARDS TO THEIR FAMILY AND SCHOOL PEERS. IN ADDITION, IT WAS ALSO OBSERVED THAT THE DEVELOPMENT OF AFFECTIVE BONDS BETWEEN PATIENT AND ANIMAL CAN IMPROVE THE EFFECTIVENESS OF THE TREATMENT FOR CONDITIONS PARALLEL TO ANXIETY AND DEPRESSION. BESIDES AAT HELPING WITH MOTOR AND PSYCHOLOGICAL DEVELOPMENT IT ALSO ASSISTS WITH THE PATIENT-THERAPIST BOND SINCE IT SOFTENS THE FIRST CONTACT€™S PRESSURE AND INTENSITY THAT THE CHILD MAY FEEL. MOREOVER, AAT IS BECOMING MORE FREQUENT, HOWEVER, THERE ARE STILL HINDRANCES THAT HAVE TO BE MANAGED, NAMELY, ANIMAL TRAINING AND CARE, POSSIBLE ALLERGIES THE PATIENT MIGHT CARRY, THE COMPLEX INFRASTRUCTURE THE METHOD DEMANDS AND THERE MIGHT BE RELATIONSHIP RESISTANCES. TO SUMMARIZE, AAT IS A PROMISING TECHNIQUE FOR THE CARE OF NON-NEUROTYPICAL CHILDREN, THUS, FURTHER SCIENTIFIC DISCUSSIONS ARE OF THE UTMOST IMPORTANCE FOR ITS CONSOLIDATION AND WIDESPREAD DEPLOYMENT.